2015
DOI: 10.5130/ajceb.v12i4.2808
|View full text |Cite
|
Sign up to set email alerts
|

Core skills requirement and competencies expected of quantity surveyors: perspectives from quantity surveyors, allied professionals and clients in Nigeria

Abstract: Deployment of appropriate skills and competencies is crucial and germane to the development and continuous relevance of any profession. In the built environment, the art of selecting the required skills and competencies expected of quantity surveyors and understanding the inherent dependencies between them remains a research issue. The purpose of this study was to determine the skill requirements and competencies expected of quantity surveyors. A structured questionnaire was administered among quantity surveyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 7 publications
2
75
0
1
Order By: Relevance
“…Especially for the reason that of the principles and ethics guiding the quantity surveying practitioners according to Dada and Jagboro [3] however, this discovery of formality in business agreement makes this study conclude that there is high survival rate for any quantity surveyor that ventures into this sector.…”
Section: Mode Of Business Agreement Between the Quantity Surveyor Andmentioning
confidence: 87%
See 2 more Smart Citations
“…Especially for the reason that of the principles and ethics guiding the quantity surveying practitioners according to Dada and Jagboro [3] however, this discovery of formality in business agreement makes this study conclude that there is high survival rate for any quantity surveyor that ventures into this sector.…”
Section: Mode Of Business Agreement Between the Quantity Surveyor Andmentioning
confidence: 87%
“…31 of 1986 gave legal backing to it and also set up the Quantity Surveying Registration Board of Nigeria (QSRBN) to regulate it [3]. The level of awareness and patronage level by clients engaging their services in the informal sector was found to be low from previous studies; Babalola [4].…”
Section: Conceptualizing the Informal Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no clearly defined focus for these skill and competence requirements. Subsequently, Dada and Jagboro (2012) in their study on an exploratory survey that investigated the attributes of quantity surveyors skills and competencies identified twenty one skills and fifteen competence areas. The identified twenty one skill variables are: computer literacy, building engineering, information technology, economics, measurement/quantification, knowledge of civil/heavy engineering, professional practice, construction law, interpersonal skill, knowledge of mechanical and electrical services engineering, financial skill and leadership skill, communication skill, managerial skill, marketing/business skill, knowledge about international trading, investment analysis, mapping/surveying, actuarial science, gas/petrochemical engineering and solid mineral engineering.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study attempts to make a useful contribution in this context. The study, which is a follow up to an exploratory survey that investigated the attributes of quantity surveyors skills and competencies (findings reported in Dada and Jagboro, 2012), used the principal component analysis to explore and detect the underlying relationship among the identified skills and competencies required of quantity surveyors. The study aims at reducing the complex and multiple categorizations of the identified skills and competencies required of quantity surveyors into clearly defined principal components.…”
Section: Introductionmentioning
confidence: 99%